FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016 - Citra Aglia Hapsari, 13.05.52.0024; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2018)
The aims of this study is to examine the effect of Profitability, Liquidity, Business Risk,Sales Growth on Capital Structure. This study uses conducted in Indonesia stock exchange by using unit of analysis of manufacturing company which have go public. The sampling method used purposive sampling with periode from 2014 to 2016. The data are processed as many 232 companies. The thechnique of data testing using multiple linear regression analysis. The result of research shows that Liquidity has negative effect to capital structure, Sales Growth has positive effect to capital structur Profitability, and Business Risk has no effect on capital structure e. Keyword :profitability, liquidity, sales growth , and business risk